Detection of Lymph Node Metastases with SERRS Nanoparticles. - Spaliviero, Massimiliano; Harmsen, Stefan; Huang, Ruimin; Wall, Matthew; Andreou, Chrysafis; Eastham, James; Touijer, Karim; Scardino, Peter; Kircher, Moritz; Wall, Matthew A; Eastham, James A; Touijer, Karim A; et al. (Molecular Imaging & Biology, 2016)
Purpose: The accurate detection of lymph node metastases in prostate cancer patients is important to direct treatment decisions. Our goal was to develop an intraoperative imaging approach to distinguish normal from metastasized lymph nodes. We aimed at developing and testing gold-silica surface-enhanced resonance Raman spectroscopy (SERRS) nanoparticles that demonstrate high uptake within normal lymphatic tissue and negligible uptake in areas of metastatic replacement.Procedures: We evaluated the ability of SERRS nanoparticles to delineate lymph node metastases in an orthotopic prostate cancer mouse model using PC-3 cells transduced with mCherry fluorescent protein. Tumor-bearing mice (n = 6) and non-tumor-bearing control animals (n = 4) were injected intravenously with 30 fmol/g SERRS nanoparticles. After 16-18 h, the retroperitoneal lymph nodes were scanned in situ and ex vivo with a Raman imaging system and a handheld Raman scanner and data corroborated with fluorescence imaging for mCherry protein expression and histology.Results: The SERRS nanoparticles demonstrated avid homing to normal lymph nodes, but not to metastasized lymph nodes. In cases where lymph nodes were partially infiltrated by tumor cells, the SERRS signal correctly identified, with sub-millimeter precision, healthy from metastasized components.Conclusions: This study serves as a first proof-of-principle that SERRS nanoparticles enable high precision and rapid intraoperative discrimination between normal and metastasized lymph nodes.